The employability skills of marketing and finance graduates / Ida Izumi Abdollah ... [et al.] - Abdollah, Ida Izumi; Omar, Noraida; Daud, Mohd Ghazali; Abg Mohar, Abg Hamizam (2010)
Due to today's business challenging competitive environments, organizations continue to focus on adaptation, cost reduction, increased productivity, new markets, new products and services as a mean to compete and survive in the industry. Organization choices with regard to recruitment and training are largely being driven by these business strategy directions. In this environment employees need to play proactive roles to be able to support the increased competitiveness, innovation, flexibility and client focus.